ANALISISKEPUASANKONSUMENTERHADAPAKSESORIPERAK(StudiKasusNikeishaSilver) THEANALYSISOFCONSUMERSATISFATIONONSILVERACCESSORIES(CaseonNikeishaSilver) - Muhammad Ridwan (Konsentrasi Manajemen Pemasaran Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2012)
AbstractConsumersatisfaction(CS)istherequirementsformarketingcampaignsuccesfull.CSmeasurementcouldbedevelopedaccordingtothespecificfirms.Inthisstudy,CSwasdetermineby:1)performance,2)feature,3)reliability,4)durability,5)aestetic,and,6)estetic.Theresearchobjectissilverhandycraft.Thesampleisthesilverhandycraftcustomerasmanyas50units.Basedontheresults,itisknownthatoverallmeanmeasureis3,9thatindicatesthatconsumersatitsfactionlevelismorethangood.Basedontheresults,itisreccomendedtoenhancetheproductcreativitytokeepconsumersatisfactionbemanagedanddeveloped.Keywords.ConsumerSatisfation,Hadycraft,NikeishaSilver.